Pengaruh Penggunaan Video Pembelajaran Interaktif Terhadap Kemampuan Pemahaman Konsep Siswa Pada Materi Sudut di SD Negeri 83 Palembang - Sari, Putri Septa (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The problem in this research is the lack of students’ ability to understand concepts at SD Negeri 83 Palembang. This research aims to find out whether there is an effect of using interactive learning videos on the ability to understand concepts in corner material at SD Negeri 83 Palembang. The subjects of this research are students of class IVA & IVC, the method used in this research is a quantitative method with the research type True Experimental Design. Data collection techniques use tests, observation and documentation. The data analysis technique uses the Independent Sample T-test. Based on data analysis, t-count = 2.223 > t-table = 1.998, so HO is rejected. So, it can be concluded that there is an influence of the use of interactive learning videos on students’ ability to understand concepts in corner material at SD Negeri 83 Palembang.